Parametric Study of Semi Submersible Responses - Maidin, Zareina Bt Maidin (2010)
Semi submersibles are being increasingly used for deep water oil and natural gas development as they have better motion characteristics as compared to drill ships and jacket structure due to their configuration and economical value. The knowledge of motion response of the semi submersible under wave excitation force is of importance in view of the workability and safety. This paper presents parametric studies to find out the effect of various parameters on the motions of the semi submersible model and to identify the crucial parameter in designing a semi submersible with a favorable motion behavior. To begin with, structural properties of Ocean America rig with 4 columns had been chosen. However, a few alterations in dimensions were made such as column diameter and pontoon size. A wave spectrum analysis was done by using the application of Pierson-Moskowitz (1964) method and a wave profile was generated based on the wave spectrum produced. Then, an analysis of wave excitation forces acting on the structure designed was computed by applying the Morison equation. Subsequently, its motion response in surge and heave due to regular and random wave was analyzed based on the linear diffraction theory and Morison equation. An analysis of surge and heave responses towards varying water depth and draft were performed. It was found that the water depth in deep water has insignificant effect on the surge and heave responses. Apparently, when draft increases, surge and heave motion decrease. In addition, by varying the draft, it affects more on heave motion than it did for surge.